Deutschland im Herbst - Böll, Heinrich 1917-1985 (Kinowelt Home Entertainment, 2004)
A collective film by many of Germany's top directors chronicling seven weeks of political terrorism by the Red Army Faction and political repression in Germany during the fall of 1977. It begins with the kidnap and murder of industrialist Hans- Martin Schleyer and ends with the deaths of three imprisoned Baader-Meinhof terrorists.
Bildformat: 1.66:1 (Letterbox)
Orig.: Bundesrepublik Deutschland 1977/78
Enth. Interviews mit Volker Schlöndorff und Juliane Lorenz ; Zeittafel
Orig.: BRD 1977/78
Keywords: Geschichte 1977; Baader-Meinhof gang -- Drama; Documentary films; Feature films; Terrorists -- Germany (West) -- Drama; Terrorismus; Deutschland -- Bundesrepublik; Film; DVD-Video